Investigating online psychological treatment for adolescents with a visible difference in the Dutch YP Face IT study: protocol of a randomised controlled trial - Marije van Dalen; Suzanne G M. A Pasmans; Marie-Louise Aendekerk; Irene Mathijssen; Maarten Koudstaal; Reinier Timman; Heidi Williamson; Manon Hillegers; Elisabeth M W. J Utens; Jolanda Okkerse (BMJ Open)
Introduction This paper outlines the study protocol for the Dutch Young People (YP) Face IT Study. Adolescents with a visible difference (ie, disfigurement) often experience challenging social situations such as being stared at, receiving unwanted questions or being teased. As a consequence, some of these adolescents experience adverse psychosocial outcomes and appearance-related distress. To address this appearance-related distress, an online psychotherapeutic intervention, YP Face IT, has been developed. YP Face IT uses social interaction skills training and cognitive–behavioural therapy. The Dutch YP Face IT Study tests whether this intervention is effective in reducing social anxiety and improving body esteem.Methods and analysis Participants are adolescents aged 12–18 with a visible difference and experiencing appearance-related distress. In this two-armed randomised controlled trial, 224 adolescents will be randomised to care as usual or YP Face IT. Adolescents will complete questionnaires at baseline, at 13 weeks and at 25 weeks. Primary outcomes are differences in social anxiety and body esteem between YP Face IT and care as usual. Secondary outcomes are differences in aspects of self-worth, perceived stigmatisation, health-related quality of life, life engagement, appearance-related distress and depressive symptoms between the two groups.Ethics and dissemination Research ethics approval was obtained from the medical ethics review committee in Rotterdam (reference number MEC-2018-052/NL63955.078.18). Findings will be disseminated through academic peer-reviewed publications, conferences and newsletters to patient associations and participants of the study.Trial registration number The Netherlands Trial Register (NL7626).